Using Bronfenbrenner’s Ecological Approach to Understand Academic Advising with International Community College Students - Leaf Zhang, Yi (Journal of International Students, 2018)
This study focuses on advising international students in a Texas community college. Guided by Bronfenbrenner’s ecological model, I explored how academic advising with international students was shaped by individual backgrounds and environmental influences. I utilized a qualitative research design and analyzed information collected from interviews with 20 academic advisors and 15 international students at the community college. The findings of the study revealed factors in each subsystem of the model that may exert an important impact on international students’ experiences in advising and academic success. The findings can provide a valuable lens for advisors to better understand the challenges of working with international students and unveil forthcoming experiences for prospective international students